Reactions of 1-Amino-5-benzoyl-4-phenyl-1H-pyrimidine-2-thione with Carbonyl Reactives - ONAL, ZULBIYE (Asian Journal of Chemistry, 2010)
The 1-amino-5-benzoyl-4-phenyl-1H-pyrimidine-2- thione (1) was obtained by starting from 4-benzoyl-5- phenyl-2,3-furandione and acetophenonthiosemicarbazone. In this study, the investigations were extended to reactions of the compound 1 with ethylacetoacetate, benzalacetophenone, cyanoacetic acid, benzyl and acetylchloride (2a-e). Thus, some new pyrimidine derivatives (3a-e) were synthesized. The structures of these compounds were determined by elemental analysis, IR, 1H NMR spectroscopic measurements.